KORELASI KOMPOSISI UNSUR TERHADAP SIFAT TERMAL SERBUK BAHAN BAKAR U-ZrHX - Masrukan; Alhasa, M. Husna; Yanlinastuti, Yanlinastuti (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Analysis has been conducted to determine the composition correlation on the thermal properties of the powder fuel U-ZrHx. U-ZrHx powder made from the process hydriding U-Zr ingot, where the ingot is the result of U-Zr and Zr U metal melting. In this experiment made three variations of powders, namely U-35ZrHx, U-45ZrHx, and U-55ZrHx. Need for determination of the thermal properties of Zr was to determine the effect of the nature of the transformation of Zr levels of heat from the fuel. At first, U and Zr metal is melted in electric arc furnaces to produce ingot U-Zr. U-Zr ingot then made powder with hydridring-milling techniques to produce U-Zr powder. U-Zr powder composition analyzed using techniques spectroscopy atomic absorption (AAS) and UV-Vis spectroscopy. The results of composition analysis showed that the analysis to determine the content of U and Zr nearly all the test samples analyzed have quite a big difference between the content of U and Zr as determined by the results of the analysis of U and Zr exception analysis result in powder U-45Zr which differ only 0.609%. From the analysis of impurities obtained that nearly all the impurities that exist still meet the requirements for fuel unless the elements Fe, where elements of the existing Fe amounted to 382.912 g/g while the requirement of £ 250 mg /µg. Testing conducted heat capacity in the temperature range 35 ° C to 437 ° C showed that the capacity were greatest powder 35ZrHx U-with a value heat capacity of 0.13 J / g.oC. Meanwhile, test results obtained transition phase change that the U-45ZrHx undergo two stages of reaction with phase change. It can be concluded when seen from the content of U and Zr cannot be used for fuel, while the analysis of the content of impurities found that all the elements that are still eligible for the fuel unless the element Fe. For the analysis of the thermal properties are the heat capacity of the heat capacity of the highest values obtained in powder U-35ZrHx, while the transition from the testing phase changes shows that the U-45ZrHx undergo two stages of reaction with phase change. There is an effect of the composition on the thermal properties, where the higher the content of Zr, the value of uranium zirconium hydride heat capacity is lower.